Impact of Terrorism on KSE 100: Evidence from Karachi - SAMI UR REHMAN; QAZI SIKANDAR HAYAT; GHAYYUR QADIR (Journal of Business & Tourism, 2021)
Terrorism is a critical issue throughout the world. In Pakistan, terrorism is one of the major obstacle in the growth of economy. The purpose of the study is to analyze the impact of terrorism in Karachi on the performance of KSE 100. Overall 27 big terrorist activities are considered in four years, ranging from 2011 to 2014. The performance of Karachi stock exchange is measured from the return of KSE 100 index. Moreover, the performance of KSE 100 index against terrorism in Karachi are analyzed through event study methodology and t-test. The result of the study shows that terrorism in Karachi has no significant impact on Karachi stock exchange 100 in all estimation windows. There is a little impact of some pre-event days on post-event days. But overall there is no significant result of terrorism in Karachi on KSE 100. The result highlights that the intensity of terrorist events is an important contributor in signifying the impact of terrorist events on KSE 100 index.